Study on the Development of Fiber-Rich Noodles through the Substitution of Wheat Flour with Pregelatinized Tannia Flour (International Journal of Scientific Research and Management (IJSRM), 2024)
Traditional noodles are often criticized for their low fiber content, a component with numerous health benefits in preventing degenerative diseases. Tannia, a potential food source in Indonesia, is recognized for its richness in fiber. This study evaluated the chemical properties, cooking quality, and sensory aspects of noodles made from a composite of wheat flour and pregelatinized tannia flour (PTF). PTF, obtained by boiling tannia tuber slices at a temperature of 95°C for 10 minutes, drying, mashing, and sieving using a 60-mesh sieve, was used to substitute some of the wheat flour in dry noodles production. Substitution levels ranged from 0% (control) to 30%. Results showed a significant impact on protein, carbohydrate, and crude fiber content, as well as color, cooking quality, and sensory properties. Crude fiber increased with substitution, but above 25%, noodles exhibited lower elasticity compared to the control. In conclusion, a 25% substitution of wheat flour with PTF produced noodles with higher crude fiber content, better cooking quality, and sensory properties comparable to control noodles (without substitution). Noodles with 25% substitution had a crude fiber content of 4.89%, while control noodles were at 3.84%